Edward Behr: The Artful Eater - Davidson, Alan E (Petits Propos Culinaires, 2024)
Edward Behr: The Artful Eater: Atlantic Monthly Press, New York, 1992: 288 pp, b/w illustrations by the author, bibliography, index, 19.95.